The medical education of internship in surgery and otolaryngology in competence of recovery of deafness caused by cerumen - Silveira, Hosana Aparecida da Costa; Diniz-Júnior, José; Lima, Luciana Fontes Silva da Cunha; Brito, Antônia Elizabeth de (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2014)
The update of the Undergraduate Medicine National Curriculum Guidelines aproaches the need of trainees to able doctors to remove foreign bodies and ears irrigation. In The Federal University of Rio Grande do Norte, this training occurs during surgery internship at the Clinical Skills Laboratory. The importance of this is evident when they learn the consequences of the permanence of these materials in the external auditory meatus, such as deafness, ear infections, dizziness, tinnitus, among others. To remove these, there are various techniques and variables protocols between services.